Optimizing Library Revisit Intention in the Digital Era : The Mediating Role of User Satisfaction Resulting from Social Media Utilization: Case Study : UIN KHAS Jember - Rizka Rif’ati Farahnaz; Bambang Irawan; Isti Fadah (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
The digital era requires libraries, including the UIN KHAS Jember Library, to innovate in attracting visitors. This study aims to analyze the role of social media in encouraging visitors to return to the library, with visitor satisfaction as a mediating variable. Using a quantitative approach with a correlational design and Structural Equation Modeling - Partial Least Squares (SEM-PLS) method, this study involved 160 active students from UIN KHAS Jember who had interacted with the library's social media as respondents selected through purposive sampling. The analysis results indicate that social media significantly and positively influences library user satisfaction (path coefficient = 0.697), and library user satisfaction has a very strong and significant influence on the intention to revisit (path coefficient = 0.797). However, it was found that social media does not have a significant direct influence on the intention to revisit, but is fully mediated by library user satisfaction. This means that social media acts as a catalyst to enhance library user satisfaction, and it is this satisfaction that serves as the primary driver for them to revisit.